Control judicial de la motivación de los laudos arbitrales: Análisis de la jurisprudencia y propuesta - Velásquez Meléndez, Raffo (Pontificia Universidad Católica del Perú, 2025)
In this paper, the author conducts a critical analysis of the practice adopted by the Commercial Chambers of Lima, which have been requiring arbitral awards to contain reasoning comparable to that of judicial decisions, relying on an extensive and debatable interpretation of Article 61.1.b of the Arbitration Law, despite the fact that both jurisdictions respond to inherently different natures.To this end, the author conducts a rigorous study of the doctrinal sources, the main national and foreign scholarly contributions, as well as the case law of the Commercial Chambers and the Constitutional Court, together with the applicable legislative framework. In particular, the study addresses the absence of an express ground for annulment of arbitral awards based on defects in reasoning, and advances an interpretative alternative to address this issue without resorting to questionable normative extensions.

En el presente trabajo el autor realiza un análisis crítico de la práctica adoptada por las Salas Comerciales de Lima, las cuales vienen exigiendo que los laudos arbitrales cuenten con una motivación equiparable a la de las resoluciones judiciales, basándose en una interpretación extensiva y discutible del artículo 61.1.b de la Ley de Arbitraje, pese a que ambas jurisdicciones responden a naturalezas distintas. Para ello, el autor realiza un estudio riguroso de los formantes doctrinales, los principales aportes nacionales y extranjeros, así como la jurisprudencia de las Salas Comerciales y del Tribunal Constitucional, además del marco legislativo aplicable. En particular, aborda la ausencia de una causal expresa de anulación de laudo por vicios de motivación, y se propone una alternativa interpretativa que permita atender a dicho problema sin recurrir a extensiones normativas cuestionables.
Judicial control of the reasoning of arbitration awards: Analysis of case law and proposal
Keywords: Duty to provide reasons; Defects in reasoning; Annulment of arbitral award; Deber de motivación; Vicios de motivación; Anulación de laudo; https://purl.org/pe-repo/ocde/ford#5.05.00